Pengaruh Interprofesional Teamwork IGD Terhadap Patien Safety: A Systematic Rivew - Evy Elita Turnip; Ni Luh Widani (Malahayati Nursing Journal, 2025)
ABSTRACT A hospital is a health service institution that is provided to an individual, family or group in a comprehensive manner by providing inpatient, outpatient, and emergency services. Interprofessional Collaboration (IPC) is a partnership between health workers who have different professional backgrounds and work together to solve health problems and provide health services and achieve common goals. Interprofessional collaboration occurs when various medical professionals work with families, patients and communities to provide comprehensive and high-quality care. This research method is a literature review study using PRISMA. The database used as a source consists of Google Scholar, ProQuest. This study uses the PICO strategy in searching for articles in electronic databases. Based on the results of the article selection, it is known that after entering keywords into the specified database, the results of the identification of 3,818 articles were obtained. Patient safety as an important part of nursing services because patient safety is a variable for measuring and evaluating the quality of nursing services that have an impact on health services. Patient safety is a fundamental and important component in providing health services in hospitals Keyword: Interprofessional Teamwork, Patient Safety  ABSTRAK Rumah Sakit adalah institusi pelayanan kesehatan yang diberikan terhadap seseorang, keluarga atau kelompok secara paripurna dengan menyediakan pelayanan rawat inap, rawat jalan, dan gawat darurat. Interprofessional Collaboration (IPC) merupakan kemitraan antar tenaga kesehatan yang memiliki latar belakang profesi berbeda dan saling bekerja sama untuk memecahkan masalah kesehatan dan menyediakan pelayanan kesehatan serta mencapai tujuan bersama. Metode penelitian ini adalah studi literature review menggunakan PRISMA. Database yang digunakan sebagai sumber terdiri dari Google Scholar, ProQuest. Penelitian ini menggunakan strategi PICO dalam menelusuri artikel pada data base elektronik. Berdasarkan hasil seleksi artikel diketahui bahwa setelah meakukan keyword ke dalam data base yang telah ditentukan, didapatkan hasil identifikasi artikel sebanyak 3.818 artikel. Keselamatan pasien sebagi bagian penting dalam layanan keperawatan karena keselamatan pasien merupakan suatu variabel pengukuran dan evaluasi mutu layanan keperawatan yang berdampak terhadap pelayanan kesehatan. Keselamatan pasien merupakan komponen yang mendasar dan penting dalam pemberian layanan kesehatan di rumah sakit. Salah satu Upaya yang dapat meningkatkan keselamatan pasien ialah terlaksananya Interprofesional Collaboration. Kata Kunci: Kolaborasi Interprofessional, Keselamatan Pasien.